Restrições de liquidez combinadas com liquidez de carteiras em fundos de ações brasileiros - Borges Junior, Dermeval Martins (2017)
Investment funds are subjected to the liquidity needs of their quotaholders, which may lead the fund manager to dispose assets at inopportune times and inappropriate prices in order to satisfy the redemption requests. To avoid such situations, the funds usually establish mechanisms that discourage or limit the liquidity of quotaholders, called liquidity constraints. The liquidity constraints, when prevent the sudden exit of investors, enable the funds to operationalize the constituted planning and provide greater liberty for the managers investment strategies, functioning as an incentive to seek illiquid opportunities with better returns in their portfolio composition. Thus, this work aims to analyze the relation between liquidity constraints and the liquidity of subjacent assets of Brazilian equity funds, as well as the effect of the interaction between portfolio liquidity and liquidity constraints on performance. For this, secondary data were collected in the Economatica and SI-ANBIMA databases regarding the liquidity constraints, portfolio liquidity, performance and characteristics of the funds. The sample contained all the Brazilian equity funds with investments in stocks listed in BM&FBovespa or in quotas of other equity funds and that presented information about the composition of their portfolios between the period from 2009 to 2016. The data were analyzed by descriptive statistics and application of linear regressions models for panel data. The main results indicated that liquidity constraints positively impact the performance of equity funds. Similarly, liquidity constraints were positively related to the general illiquidity of the funds’ portfolios, suggesting that, from these mechanisms, the funds exploit illiquid investments in stocks and quotas of other funds. When verifying if the investment in illiquid assets by the equity funds implies in better performance, from liquidity premia, the results were inconclusive. In view of the above, this study contributes to the literature on the subject, fundamentally, by expanding the findings concerning not only the simple relation between liquidity constraints and the equity funds’ performance, but also the way in which these restrictions impact the options of their investment.